2000
DOI: 10.2337/diabetes.49.5.708
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of type 1 diabetes by a coxsackievirus infection requires a preexisting critical mass of autoreactive T-cells in pancreatic islets.

Abstract: Coxsackievirus infections have been proposed as an environmental trigger for the development of T-cell-mediated autoimmune (type 1) diabetes by either providing a molecular mimic of the candidate pancreatic ␤-cell autoantigen GAD or inducing bystander inflammation in the pancreas. In this study in the NOD mouse model, we found that infection with a pancreatrophic coxsackievirus isolate can accelerate type 1 diabetes development through the induction of a bystander activation effect, but only after a critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
170
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(196 citation statements)
references
References 16 publications
22
170
1
1
Order By: Relevance
“…Diabetes development after enterovirus infection in the most commonly used experimental model, the NOD mouse, is dependent on the already established prediabetic phase including insulitis [15][16][17]31], which in the NOD mouse occurs after maternally transferred antibodies may have waned [32]. This is in contrast with humans in whom islet autoantibodies may already appear before the disappearance of maternal antibodies [23,33,34].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Diabetes development after enterovirus infection in the most commonly used experimental model, the NOD mouse, is dependent on the already established prediabetic phase including insulitis [15][16][17]31], which in the NOD mouse occurs after maternally transferred antibodies may have waned [32]. This is in contrast with humans in whom islet autoantibodies may already appear before the disappearance of maternal antibodies [23,33,34].…”
Section: Discussioncontrasting
confidence: 41%
“…[6,12]). Furthermore, experimental animal models have indicated that enterovirus infections can cause direct beta cell damage [13,14] and alter disease progression in the NOD mouse model [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the timing of a Coxsackievirus infection, rather than a simple documentation of its presence or absence, has important implications in the development of diabetes in NOD mice. In this animal model, CVB4 infection can accelerate the development of Type I diabetes only after a critical amount of autoreactive T cells have accumulated at the periphery of the islets [32]. Based on this finding, we suppose that in humans, like in rodents, the timing of a Coxsackievirus infection is a critical factor in the development of diabetes by activating autoreactive T cells already present in the circulation and possibly in proximity to the islets.…”
mentioning
confidence: 92%
“…53 The observed exacerbation of T1D requires both uptake and activation of antigen-presenting cells 54 as well as presence of a pre-existing critical mass of autoreactive T cells within the islets of Langerhans. 55 This later observation is intriguing since it demonstrates that CVB4 might rather accelerate an ongoing autodestructive process than de novo induce T1D. It is interesting to note that even infection of regular wild-type mice with CVB4 causes insulitis, low serum insulin levels and moderately elevated blood glucose values.…”
Section: Virus Infection and Type 1 Diabetes U Christen And Mg Von Hementioning
confidence: 99%